Analisa sifat mekanik material logam melalui pemodelan dan simulasi uji tarik berdasarkan metode elemen hingga - Susanto, A.; Mahendra, M.T.; Andriyani, R.P. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2024)
Mechanical properties of material are attributes that should be known by engineers and product designers to determine the suitability of the structure being designed. One of the ways to determine the mechanical properties of a material is generally conducted by well-known tensile test. By the test, it will inform the elastic, plastic and fracture areas are known in the strain-stress diagram. Apart from that, the yield strength and maximum tensile strength can also be observed. The obstacle factor in experimentally tensile testing is the expensive costs, both for renting and procuring a tensile testing machine, which is called universal testing machine (UTM). This research aims to provide an alternative tensile test method, namely modeling and simulation techniques based on the finite element method (FEM). The workpiece material applied was ST37 Steel. This material is widely utilized in various types of industry, including the automotive, railway, and construction industries. The results show that the simulation can display all events that tensile tests may not be able to display experimentally, such as information on stress distribution and also elongation during the test. In addition, the mechanical properties of the ST37 material were obtained, including the yield strength of the material (yield point, Y) and the maximum tensile strength (ultimate tensile strength, σmax) which were 812.3 and 928.1 MPa, respectively.